RESPON STEK PUCUK MAHONI (Swietenia macrophylla King) TERHADAP PEMBERIAN ZAT PENGATUR TUMBUH BERBAHAN ORGANIK - Maria Kasih Karunia Nirmala Pab; Wilhelmina Seran; Shirly S Oematan (Wana Lestari, 2021)
Mahogany (Swieteniamacrophylla King) is a type of forestry plant that is often used as a raw material in the timber industry and as a land rehabilitation plant. Vegetative propagation by shoot cutting becomes one of the alternatives way to cultivate Mahogany to anticipateits short-life seeds. The treatment of organic Growing Regulators on Mahogany shoot cutting is expected to increase the success of shoot cutting. This research was conducted to find out the influence of organic Growing Regulators substances such as Shallot Extract, Coconut Water, and Cow Urine, on the growth of mahogany shoots cuttings. The research method used Complete Random Design (RAL) with 13 treatments that are Control treatment (Aquades), Growing Regulators substances Shallot Extract, Coconut Water, and Cow Urine with 25%, 50%, 75%, 100% contingency respectively. The results showed that the treatment of organic Growing Regulators substances (Shallot Extract, Coconut Water and Cow Urine) significantly affected (95%) on the variable observation of the percentage of life and the increase in the length of mahogany shoots and significantly (99%) affected on the parameters such as the number of leaves and the length of mahogany shoots cuttings, but had no significantly affected on the period of its shoots growth. The organic Growing Regulators Shallot Extract treatment showed the highest influence on 3 observation variables. Treatment Connotation of Shallot Extract 100% is a treatment that shows the best growth compared to other treatments because it shows a high influence on almost all observed variables.